Family business internationalization opportunities and obstacles from an entrepreneur's perspective : a case study of the creative industry - Kemppainen, Karoliina (2011)
The purpose of this study is to analyze how the internationalization process of a family business in the creative industry can be promoted in Finland. The context of the thesis consists of family business and creative industry and the phenomenon investigated is the internationalization process and its services thus constituting the theoretical part of the study. The study is trying to find an answer to the primary question: How can the internationalization process of a family business be promoted in Finland? A qualitative case study was chosen as a research method since the empirical data consists of two separate case studies in the creative industry. This case study has a narrative approach in illustrating opportunities and obstacles of internationalization. Primary data collection method has been semi-structured theme interviews and in addition, data has been collected through seminars, e-mails and reading financial documents. In this study the analysis has been executed by categorizing information by adapting Miles’ and Huberman’s (1994) thematic conceptual matrix. According to this case study, funding is the biggest challenge above all others for small and medium sized family enterprises (SMFE) in the creative industry. This case study suggests that there is a huge information asymmetry between financiers and enterprises when it comes to the valuation of intangible assets of a company in the creative industry. SMFEs in the creative industry have troubles to get adequate funding for internationalization since present funding instruments do not suit to the needs of know-how companies. In order to promote family business internationalization in the creative industry new funding instruments have to be developed. Such possibilities could be a balance appreciation of IPR or a balance-independent funding model, where IPR would be appreciated directly as a security. Public guidance and funding services and the use of EU projects must be renewed so as to serve entrepreneurs and companies better. In addition, education development has to respond to the needs of business life.